A systematic literature review on the relationship between basic psychological need satisfaction and exercise intention - Wang, Jingyi; Ali, Syed Kamaruzaman Bin Syed (Edelweiss Applied Science and Technology, 2025)
This systematic review examines how Basic Psychological Need Satisfaction (BPNS), rooted in Self-Determination Theory (SDT), influences exercise intention (EI), and assesses the validity of related measurement instruments within exercise contexts. SDT posits autonomy, competence, and relatedness as fundamental needs for sustained motivation, with recent research highlighting novelty and variety as potential extensions. Following PRISMA guidelines, a comprehensive search across Web of Science, Scopus, and PubMed identified 24 peer-reviewed empirical studies published between 2013 and 2023. Among these, six studies evaluated BPNS measurement tools, generally supporting their multidimensional reliability and construct validity. The remaining 23 studies explored links between BPNS components and EI, consistently identifying autonomy and competence as key predictors across various populations, including university students, adolescents, and clinical groups. Novelty and variety emerged as context-dependent factors, particularly salient in gamified and technology-enhanced exercise settings. Despite promising findings, definitional inconsistencies and a reliance on cross-sectional designs limit causal inferences and generalizability. This review highlights the pivotal role of autonomy and competence in shaping exercise intention and advocates for longitudinal, cross-cultural investigations and standardized measurement practices to strengthen both theoretical understanding and practical applications.